RANCANG BANGUN SISTEM INFORMASI LP3I STUDENT CARE CENTER BERBASIS WEB PADA POLITEKNIK LP3I JAKARTA KAMPUS DEPOK - Nasril Nasril; Dimas Adhitya (JURNAL LENTERA ICT, 2025)
The LP3I Jakarta Polytechnic Depok Campus has a Student Care Center (SCC) as a place for lecturers to record the results of student consultations. Currently, recording is still done manually, making it inefficient in terms of data search, storage, and report generation. Therefore, a web-based information system is needed to manage consultation data more effectively. This study aims to design and develop a web-based Student Care Center information system to support the recording and management of student complaints. The system was developed using the CodeIgniter 4 framework, with Bootstrap templates for a responsive interface, and a MySQL database for data storage. The system development method used was waterfall, which consists of analysis, design, implementation, and testing stages.